2019
DOI: 10.3390/catal9100864
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel Production from Castor oil by Two-Step Catalytic Transesterification: Optimization of the Process and Economic Assessment

Abstract: The use of biodiesel and the requirement of improving its production in a more efficient and sustainable way are becoming more and more important. In this research work, castor oil was demonstrated to be an alternative feedstock for obtaining biodiesel. The production of biodiesel was optimized by the use of a two-step process. In this process, methanol and KOH (as a catalyst) were added in each step, and the glycerol produced during the first stage was removed before the second reaction. The reaction conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 42 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…According to the literature data, among the vegetable oils and fats, the higher contents of SFAs were found in palm kernel oil (76.0%) and coconut oil (90.5%) with a dominant presence of C12:0 and C14:0 methyl esters, while lower in linseed oil (9.65%), sunflower oil (8.8%), and safflower oil (7.2%) [46]. The total content of C16:0 in analyzed herbal samples is higher than in castor [47], rapeseed, and sunflower oils [48].Presented findings are coherent with previous research on other plant species, where MUFAs were also athigher levels than SFAs (Figures 2-4). Interestingly, MUFA was the main part of FAME compositions in oils, such as sesame (42.0%), rice brain (44.0%), almond (67.9%), olive(68.2%), peanut (71.1%), and rapeseed (72.8%).…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature data, among the vegetable oils and fats, the higher contents of SFAs were found in palm kernel oil (76.0%) and coconut oil (90.5%) with a dominant presence of C12:0 and C14:0 methyl esters, while lower in linseed oil (9.65%), sunflower oil (8.8%), and safflower oil (7.2%) [46]. The total content of C16:0 in analyzed herbal samples is higher than in castor [47], rapeseed, and sunflower oils [48].Presented findings are coherent with previous research on other plant species, where MUFAs were also athigher levels than SFAs (Figures 2-4). Interestingly, MUFA was the main part of FAME compositions in oils, such as sesame (42.0%), rice brain (44.0%), almond (67.9%), olive(68.2%), peanut (71.1%), and rapeseed (72.8%).…”
Section: Resultsmentioning
confidence: 99%
“…1 Here, especially castor oil takes a prominent position and is currently evaluated as starting material for ricinoleate-based biodiesels. 2,3 To the best of our knowledge, however, the methods of the state-of-the-art almost exclusively centre around the transesterication of castor oil or the esteri-cation of ricinoleic acid. All these methods share the intrinsic disadvantage of being reversible reactions thereby necessitating large molar surpluses of the alcohol to attain signicant conversion into the desired biodiesel fatty acid methyl ester (FAME) (Scheme 1).…”
mentioning
confidence: 99%
“…Among them, C16:0 and C18:1 are the most ideal components of biodiesel. The total content of C16:0 in analyzed samples is greater than in castor [12], rapeseed and sunflower oils [13] (Table 1). The results also showed that the unsaturated fatty acid amount was greater than that of saturated fatty acids.…”
Section: Resultsmentioning
confidence: 83%